Restoring Balance to Abuse Cases: Expanding the One-Sided Approach to Teaching Domestic Violence Practice - Schulte, Katherine E. (Columbia Journal of Gender and Law, 2014)
“Balance” is an elusive concept in the domestic violence field. Equilibrium can always be threatened by tension between attorney and client, between the parties and the legal system, and, of course, between the parties themselves. Abusive relationships are inherently unbalanced; the abusive partner maintains power and control by systematically overcoming the will of the other partner, often using violence and coercion. When an abuse case enters the legal system, therefore, the playing field is anything but level.